(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study is to find out the influence of Fartlek and circuit training on VO2 max among school level cricket players. 36 male cricket players age ranged 12 to 15 years were selected from Sri Chaitanya Future Pathways School, Miyapur Campus, Hyderabad. They were divided into three groups, namely, Fartlek training (group – I), circuit training (group – II) and control (group – III). The two groups were experimented with Fartlek and circuit training respectively for 12 weeks. The collected data from the three groups prior to and post experimentation were statistically analyzed to find out the significant difference if any, by applying the analysis of covariance (ANCOVA). Since three groups were involved, the Scheffe’s test was applied as post hoc test to determine the paired mean differences, if any. In all the cases statistical significance was fixed at 0.05 levels. Twelve weeks of Fartlek and circuit training had significant increase on VO 2 max of cricket players.